Pengembangan Aplikasi Mobile Learning Untuk Meningkatkan Kemandirian Dan Prestasi Belajar Pada Mata Kuliah Rekayasa Perangkat Lunak - Rosyadi, Muhammad Bachtyar (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to produce learning media, namely mobile learning applications that are suitable for use for software engineering courses for fifth semester students, determine the effect of mobile learning application learning media on student achievement in fifth semester, and determine the effect of mobile learning application learning media on student learning independence semester V.This research is an R & D research with ADDIE design which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The developed application was tested on 26 students of the fifth semester of informatics engineering study program, Muhammadiyah University of Gresik. Data collection was carried out by giving validation sheets to material experts, media experts, course lecturers to assess the feasibility of the product as well as student response questionnaires to provide input for the developed product. Procurement of pretest and posttest to determine the increase in learning outcomes and filling out questionnaires by students, observations in class, and interviews to determine the increase in students' learning independence.The results showed that the product resulting from the development of the media was declared feasible based on the assessment of experts, lecturers and student response questionnaires in the good category, the developed learning media could improve the learning achievement of software engineering courses with a gain value of 0.6 or in the medium category, and The developed learning media can increase the learning independence of students with a gain value of 0.2 or in the low category.